International Journal of Applied and Computational Mathematics - Saha Ray, Santanu; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer.)
This is a broad-based journal, covering all branches of computational, applied and numerical mathematics. Papers containing new ideas, creative approaches and/or innovative applications are welcome. Papers that study novel theory, analysis and applications of innovative analytical and numerical techniques are sought.
Keywords: Nuclear energy; Operations research; Decision making; Applied mathematics; Engineering mathematics; Computer mathematics; Mathematical models; Physics; Applications of Mathematics; Mathematical Modeling and Industrial Mathematics; Operations Research/Decision Theory; Theoretical, Mathematical and Computational Physics; Computational Science and Engineering; Nuclear Energy